Multivariate Analysis in Lentil (Lens culinaris L.) - Jewel, AA; Chowdhury, AK; Alam, AKMM; Latif, MA; Hassan, MM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Genetic divergence among 22 genotypes of lentil was estimated using D2 and principal component analysis. The genotypes under study fell into four clusters. The intra-cluster value was the maximum in cluster I and the minimum in cluster II. The inter-cluster distance was larger than the intra-cluster distance in all the cases suggesting the wider genetic diversity among the genotypes of different groups. The inter-cluster value indicated maximum distance between cluster I and II than cluster III and IV. Thus the genetically diverged genotypes of the clusters could be used as parent in hybridization program to get desirable genotypes. Cluster I had the highest mean for days to maturity, plant height, pods/plant and per plot yield while cluster II and III had the highest days to first flowering and 100 seed weight, respectively. Genotypes with these characters in respective groups would, therefore, offer a good scope of improvement of lentil through selection. Key words: Lentil; cluster analysis; divergence; hybridization DOI: http://dx.doi.org/10.3329/bjpbg.v23i1.9312 BJPBG 2010; 23(1): 9-12